2010
DOI: 10.1111/j.1365-2753.2009.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between continuity of care and outcomes: a systematic and critical review

Abstract: These studies validate the belief that increased provider continuity is associated with improved patient outcomes and satisfaction. Further research is required to determine whether information or management continuity improves outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
422
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(440 citation statements)
references
References 37 publications
12
422
0
6
Order By: Relevance
“…23 Hence, we used insurance premiums as an indicator to represent patients' socioeconomic status. 39 In addition, despite measuring COC before health care outcomes, as suggested by a previous study, 53 the problem of temporal ambiguity between COC and health care outcomes might not be completely avoided. We recommend that this issue should be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…23 Hence, we used insurance premiums as an indicator to represent patients' socioeconomic status. 39 In addition, despite measuring COC before health care outcomes, as suggested by a previous study, 53 the problem of temporal ambiguity between COC and health care outcomes might not be completely avoided. We recommend that this issue should be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the outpatient setting, greater continuity has been associated with better hypertensive control, lower risk of hospitalization, fewer emergency department visits, higher patient satisfaction, and higher physician satisfaction. [1][2][3][4] Achieving continuity is difficult in the inpatient setting, where care must be provided continuously. Fletcher et al showed that between 1996 and 2006, Medicare patients experienced declining levels of physician continuity during their hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…31 There is evidence that increased continuity is associated with improved outcomes and satisfaction. 35,36 Although continuity may be important to all health service users, it is thought to be particularly important for those with complex health needs such as dementia, long-term conditions, multimorbidity and frailty. 37,38 Dementia is a long-term condition characterised by progressive deterioration and dependency.…”
Section: Continuity Of Carementioning
confidence: 99%